2004
DOI: 10.1042/bj20031253
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent internalization of particles via the pathways of clathrin- and caveolae-mediated endocytosis

Abstract: Non-phagocytic eukaryotic cells can internalize particles <1 microm in size, encompassing pathogens, liposomes for drug delivery or lipoplexes applied in gene delivery. In the present study, we have investigated the effect of particle size on the pathway of entry and subsequent intracellular fate in non-phagocytic B16 cells, using a range of fluorescent latex beads of defined sizes (50-1000 nm). Our data reveal that particles as large as 500 nm were internalized by cells via an energy-dependent process. With a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

120
1,931
12
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 2,493 publications
(2,098 citation statements)
references
References 48 publications
120
1,931
12
10
Order By: Relevance
“…Inorganic particles below 100 nm were found to be internalized to a greater extent and to reduce viability. 25,27 However, it has also been suggested that an inflection point on the particular internalization route is apparent at a size of approximately 200 nm, 28 which is also corroborated in our study. It is for that reason that when designing a micro-or nanoparticulate drug delivery system it is advisible to avoid the thresholds that were found to have a greater impact on cell viability.…”
Section: Resultssupporting
confidence: 91%
“…Inorganic particles below 100 nm were found to be internalized to a greater extent and to reduce viability. 25,27 However, it has also been suggested that an inflection point on the particular internalization route is apparent at a size of approximately 200 nm, 28 which is also corroborated in our study. It is for that reason that when designing a micro-or nanoparticulate drug delivery system it is advisible to avoid the thresholds that were found to have a greater impact on cell viability.…”
Section: Resultssupporting
confidence: 91%
“…Following inhibitor toxicity studies, confocal microscopy was employed to assess the specificity of the inhibitors in relation to the uptake of molecules known to taken up by specific endocytic routes, Human transferrin (hTF) 38 and lactosylceramide (LacCer). 39 hTF is known to be taken up via CDE while LacCer is internalized via CIE where is associated with lipid rafts. 40 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…76 This pathway is of considerable interest in particular for molecular conjugates containing pathogen-derived trafficking peptides, since many pathogens (SV40 and cholera toxin included) are thought to use the caveolar pathway to evade degradation in the lysosomes. 77 Using different sized microspheres, Rejman et al 78 showed that molecular size can dictate whether cell entry occurs by clathrin or caveolae-mediated endocytosis. Microspheres of 200 nm in diameter or less entered cells through clathrin-coated pits by a microtubule dependent pathway.…”
Section: Caveolae-mediated Endocytosismentioning
confidence: 99%